FINANCIAL ANALYSIS IN BUDGETARY INSTITUTIONS - Gerasimova, Larisa; Parasotskaya, Natalya; Dvoretskaya, Vera (Revista Inclusiones, 2019)
The article illustrates the relevance of developing new directions in the analysis and performance evaluation techniques aimed at results-based management optimizing the use of budgetary institutions’ resources. The assessment of a state institution’s financial condition, its financial results, and risks is implemented by analysing the financial and economic activities of the budgetary institution. The article addresses the problem of determining the proper objectives of financial analysis in an institution, along with the sources of information. The authors also assess the priority methods.